The Influence of Taste Liking on the Consumption of Nutrient Rich and Nutrient Poor Foods - Liem, Djin Gie; Russell, Catherine Georgina (Frontiers in Nutrition, 2019)
Repeated consumption of high-energy nutrient poor foods can lead to undesirable health outcomes such as obesity. Taste plays an important role in food choice, and a better understanding of the links between the taste of foods, individual taste preferences, food choices and intakes will aid in our understanding of why some people might select and consume unhealthy foods. The present review focuses on three main questions: 1) do nutrient poor and nutrient rich foods significantly differ in taste profile? 2) are humans predisposed towards developing a liking or preference for certain taste profiles? 3) how are individual variations in liking of the basic taste qualities related to long term food intake and adverse health outcomes such as obesity? Results indicated that nutrient poor foods were likely to be sweet, salty and fatty mouthfeel, while the taste profiles of nutrient rich foods were diverse. Although humans are born with a universal liking for sweet and aversion for bitter taste, large individual differences exist in liking of all the basic taste qualities. These individual differences partly explain differences in short term intakes of foods varying in taste profiles. However they fail to sufficiently explain long term food choices and negative health outcomes such as obesity. Future studies should focus on how the full sensory profile of food which includes taste, smell and texture interacts with individual characteristics (e.g. taste or health motivations, taste preferences) to affect consumption of nutrient rich and nutrient poor foods.